Tunneling in the Brillouin zone: Theory of backscattering in valley Hall edge channels - Shah, Tirth; Marquardt, Florian; Peano, Vittorio (Physical Review B, 2021)
A large set of recent experiments has been exploring topological transport in bosonic systems, e.g., of photons or phonons. In the vast majority, time-reversal symmetry is preserved, and band structures are engineered by a suitable choice of geometry to produce topologically nontrivial band gaps in the vicinity of high-symmetry points. However, this leaves open the possibility of large-quasimomentum backscattering, destroying the topological protection. Up to now, it has been unclear what precisely the conditions are where this effect can be sufficiently suppressed. In the present paper, we introduce a comprehensive semiclassical theory of tunneling transitions in momentum space, describing backscattering for one of the most important system classes, based on the valley Hall effect. We predict that even for a smooth domain wall, effective scattering centers develop at locations determined by both the local slope of the wall and the energy. Moreover, our theory provides a quantitative analysis of the exponential suppression of the overall reflection amplitude with increasing domainwall smoothness.
CRIS-Team WoS Importer:2022-01-14